Brazília a modernizációs diktatúrától a hibrid posztdemokráciáig - Szilágyi István (Geopolitikai szemle, 2019)
In South America in the 1960s and 1970s the contradictions of economic, social and political structures were deepening. The excepcional states of the new militarism appeared on the continent. Formally these state systems were set up by the institutional takeover of the armed forces. The military governments strove for the total reorganization and modernization of the societies in their all ‒ economic, political and ideological ‒ territories. The break-down of the military dictatorships in South America, in the one of three semi-peripherical areas of the world, took place in the 1970s and 1980s and 1990s and it was followed by the restoration of the civil governing in the form of hybrid systems. All these processes constituted the parts of the democratization. However in those societies have been present the authoritarian enclaves and the so-called “powers that be” as well as the inherited non-elected system of institutions of the controlled democray endangering the democratic establishment. The study aims at analizing these processes, the governmental and the state structures and the Económic transformations on the ground of the Brazilian experiences.